Three-dimensional seismic performance analysis of large and complex underground pipe trench structure. Issue 150 (November 2021) - Tao, Lianjin; Ding, Peng; Lin, Hai; Wang, Hailong; Kou, Weifeng; Shi, Cheng; Li, Sicheng; Wu, Shang
Abstract: The existed 1D (dimensional) and 2D seismic analysis methods couldn't met the seismic research requirements of large and complex underground pipe trench structure (LCUP). In order to solve the problem that the seismic performance analysis of LCUP requires high 3D modeling ability and calculation equipment, an integrated seismic analysis method of "overall structure + key nodes" was proposed in this paper. Firstly, according to the research purpose, the seismic analysis strategy of LCUP was proposed, and the main factors influencing the seismic time history analysis of LCUP were analyzed one by one, and a series of accurate analysis parameters and simplified assumptions were obtained. Secondly, the 3D seismic analysis model of LCUP was established, including the overall pipe trench model and the local key nodes model, and the material parameters, boundary conditions, ground motion and calculation conditions of the model were determined. Finally, 3D seismic time history analysis was carried out for the whole structure and key joints, and the seismic performance evaluation based on mechanics and deformation was carried out. The seismic performance of the LCUP met the design requirements. The results showed that the method didn't only meet the requirements of seismic analysis accuracy and depth for complex underground space structure, but also significantly reduced the time of seismic analysis and improves the research efficiency. This research method will provide a useful reference for the seismic research of similar large complex underground structures. Highlights: The seismic analysis strategy of large and complex underground pipe trench structure is proposed. The key influencing factors of seismic analysis for large and complex underground pipe trench structure are studied. An integrated seismic analysis method of "overall structure + key nodes" is proposed. The seismic performance of large-scale irregular and complex underground pipe trench structure is evaluated.